2016
DOI: 10.3390/catal6030039
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production by Ethanol Steam Reforming (ESR) over CeO2 Supported Transition Metal (Fe, Co, Ni, Cu) Catalysts: Insight into the Structure-Activity Relationship

Abstract: Abstract:The aim of the present work was to investigate steam reforming of ethanol with regard to H 2 production over transition metal catalysts supported on CeO 2 . Various parameters concerning the effect of temperature (400-800˝C), steam-to-carbon (S/C) feed ratio (0.5, 1.5, 3, 6), metal entity (Fe, Co, Ni, Cu) and metal loading (15-30 wt.%) on the catalytic performance, were thoroughly studied. The optimal performance was obtained for the 20 wt.% Co/CeO 2 catalyst, achieving a H 2 yield of up to 66% at 400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 95 publications
3
42
0
Order By: Relevance
“…The superior activity of CeO 2 -based support can be linked to the good metals particles dispersion and the prevention of sintering phenomena; moreover, their capability to add and remove oxygen in a reversible manner facilitates carbon gasification [26]. Mobile oxygen of ceria can also activate water, with regard to the formation of hydroxyl groups, resulting in higher ESR efficiency [27]. In particular, ceria was shown to accelerate the reaction of steam and absorbed species at the metal-support interface, giving place to -O and -HO species, which are transferred to the surface carbon, thus promoting coke conversion to gaseous products (CO, H 2 , and CO 2 ) [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The superior activity of CeO 2 -based support can be linked to the good metals particles dispersion and the prevention of sintering phenomena; moreover, their capability to add and remove oxygen in a reversible manner facilitates carbon gasification [26]. Mobile oxygen of ceria can also activate water, with regard to the formation of hydroxyl groups, resulting in higher ESR efficiency [27]. In particular, ceria was shown to accelerate the reaction of steam and absorbed species at the metal-support interface, giving place to -O and -HO species, which are transferred to the surface carbon, thus promoting coke conversion to gaseous products (CO, H 2 , and CO 2 ) [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…SR is a strong endothermic process and requires an external heat sources [1,6], while auto-thermal reforming (ATR) with endothermic steaming reforming (SR) and exothermic partial oxidation reaction …”
Section: Introductionmentioning
confidence: 99%
“…Scarabello et al [46] reported that the O-vacancy in Rh/Ce-ZrO 2 promotes the oxidation of CO to CO 2 by the reaction in Equation (15) and the dissociation of water, increasing H 2 production (Equation (16) …”
Section: Effect Of the Rh-pt Ratio On The Catalytic Performancementioning
confidence: 99%
“…However, the use of ethanol/gasoline mixtures in Base metals, such as Ni [15], Co [16], and Fe [17], and noble metals, such as Pd [18], Rh [18,19], Pt [7,20], and Ir [21], supported on metals oxides to catalyze SRE have been widely studied. The nature of the catalyst and operational conditions directly affect its performance in SRE [15,22]. Ni is a widely studied catalyst due to its low cost [10].…”
Section: Introductionmentioning
confidence: 99%